Multi-Object Inventory System Using Ultra-High Frequency Radio Frequency Identification (UHF RFID) Based on Internet of Things - Faisal Candrasyah Hasibuan; Ashri Dinimaharawati; Hasbi Ash Shiddieqy; Faraday Barr Fatahillah; Axel David; Muhammad Rafindha Aslam (School of Applied Science, Telkom University, 2024)
This study develops an IoT-based inventory system that integrates UHF RFID technology with proximity sensors and an Android application to enable real-time multi-object tracking. The system automatically detects item movement direction (in/out) through sensor sequencing and provides cloud-based monitoring. Testing revealed exceptional single-object performance (100% accuracy at 1-5m distance; 1.53-1.62s avg. transmission time), but significant degradation with multiple objects, particularly beyond 3m (e.g., 5% accuracy for three objects at 5m). Although API integration enabled efficient data transmission, performance was constrained by ESP32 buffer limitations, RFID tag quality, and network stability. The solution demonstrates potential for low- to moderate-intensity inventory environments, providing a foundation for improving accuracy, although further comparative evaluation is required.